The Influence Of The Social Environment At School On The Learning Motivation Of Deaf Student - Nurul Hidayati (Educational Psychology Journal, 2025)
Inclusive education for children with special needs, especially deaf students, is a fundamental need in creating a fair and equitable education system. This article discusses the influence of the school environment on deaf students' learning motivation, focusing on the physical, social, academic and emotional aspects that support their learning process. This research uses a descriptive qualitative approach to analyze the role of a conducive school environment in improving deaf students' enthusiasm and motivation to learn at an inclusive junior high school in Surakarta. The results showed that deaf-friendly facilities, positive social support, learning methods tailored to students' needs, and an inclusive emotional environment greatly influenced their learning motivation. Factors such as the availability of hearing aids, empathic attitudes from teachers, and supportive social interactions also increase deaf students' learning motivation. Therefore, it is important for schools to provide an adaptive and inclusive environment so that deaf students can learn optimally and feel accepted in the educational environment.